Modeling and feasibility study of a dish-micro gas turbine system in different regions of Malaysia - Othman, Syariffah (2022)
Concentrated solar power (CSP) systems are a renewable energy source that can help decouple the energy mix from fossil fuel combustion and its associated environmental effects. Due to high costs, complexity, and poor dependability, existing small-scale CSP solutions (Dish-Stirling) have not entered the market. These projects intended to address the drawbacks of small-scale CSP by combining a solar dish with the compact and relatively inexpensive micro gas turbine (MGT) technology. The study's objective is to investigate the performance and viability of a 30kW dish-MGT in Malaysia. In this study, a hybrid system of solar micro gas turbine with a combustion chamber was investigated. A dish-MGT system with three main components: a concentrator, a receiver, and a micro gas turbine was the subject of this study. Matlab Simulink is used to simulate the background of the dish-MGT system and its components model. Meanwhile, the performance of the three major components was tested under three different solar irradiation conditions: low, medium, and high. Thus, five sites or locations have been chosen for this study by considering the highest Direct Solar Irradiance (DNI) and based on regions. In the northern part of Peninsular Malaysia, George Town has the highest DNI. Besides that, Subang, in the middle part of Peninsular Malaysia, Kuantan, on the east coast of Peninsular Malaysia, Senai, in the southern part of Peninsular Malaysia, and Kuching, in East Malaysia. To investigate the impact of climatic conditions on system performance and electricity generation, a thermodynamic model was built. The highest daily solar irradiation cycle outlet power for 81 m2 dish collector aperture area was 30 kW, with a solar-to-electric efficiency of 36%. Dish-MGT has a higher total yearly energy, Levelized Cost Of Energy (LCOE), and capacity factor of 87 kWh, MYR 1.01/kWh, and 33%, respectively, than a traditional dish system such as dish-Stirling. The developed model of the dish-MGT system shows that the system is technically feasible but not economically feasible and not environmentally sustainable. In conclusion, the study's findings showed that Malaysia's dish-MGT system is capable of serving local demand reliably. However, in order to improve the LCOE and reduce CO2 emissions, more work is required. The findings of this study can assist policymakers and regulators in better understanding the potential for CSP development in this country and other equatorial countries.